1-Oleyl-lysophosphatidic acid (LPA) promotes polarization of BV-2 and primary murine microglia towards an M1-like phenotype. Issue 1 (December 2016) - Plastira, Ioanna; Bernhart, Eva; Goeritzer, Madeleine; Reicher, Helga; Kumble, Vishwanath; Kogelnik, Nora; Wintersperger, Andrea; Hammer, Astrid; Schlager, Stefanie; Jandl, Katharina; Heinemann, Akos; Kratky, Dagmar; et al.
Abstract Background Microglia, the immunocompetent cells of the CNS, rapidly respond to brain injury and disease by altering their morphology and phenotype to adopt an activated state. Microglia can exist broadly between two different states, namely the classical (M1) and the alternative (M2) phenotype. The first is characterized by the production of pro-inflammatory cytokines/chemokines and reactive oxygen and/or nitrogen species. In contrast, alternatively activated microglia are typified by an anti-inflammatory phenotype supporting wound healing and debris clearance. The objective of the present study was to determine the outcome of lysophosphatidic acid (LPA)-mediated signaling events on microglia polarization. Methods LPA receptor expression and cyto-/chemokine mRNA levels in BV-2 and primary murine microglia (PMM) were determined by qPCR. M1/M2 marker expression was analyzed by Western blotting, immunofluorescence microscopy, or flow cytometry. Cyto-/chemokine secretion was quantitated by ELISA. Results BV-2 cells express LPA receptor 2 (LPA2), 3, 5, and 6, whereas PMM express LPA1, 2, 4, 5, and 6. We show that LPA treatment of BV-2 and PMM leads to a shift towards a pro-inflammatory M1-like phenotype. LPA treatment increased CD40 and CD86 (M1 markers) and reduced CD206 (M2 marker) expression. LPA increased inducible nitric oxide synthase (iNOS) and COX-2 levels (both M1), while the M2 marker Arginase-1 was suppressed in BV-2 cells. Immunofluorescence studies (iNOS, COX-2, Arginase-1, and RELMα) extended these findings to PMM. Upregulation of M1 markers in BV-2 and PMM was accompanied by increased cyto-/chemokine transcription and secretion (IL-1β, TNFα, IL-6, CCL5, and CXCL2). The pharmacological LPA5 antagonist TCLPA5 blunted most of these pro-inflammatory responses. Conclusions LPA drives BV-2 and PMM towards a pro-inflammatory M1-like phenotype. Suppression by TCLPA5 indicates that the LPA/LPA5 signaling axis could represent a potential pharmacological target to interfere with microglia polarization in disease.